2017
DOI: 10.3389/fpsyg.2017.00233
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Expectations Regarding Medical Treatment: A Critical Review of Concepts and Their Assessment

Abstract: Patients’ expectations in the context of medical treatment represent a growing area of research, with accumulating evidence suggesting their influence on health outcomes across a variety of medical conditions. However, the aggregation of evidence is complicated due to an inconsistent and disintegrated application of expectation constructs and the heterogeneity of assessment strategies. Therefore, based on current expectation concepts, this critical review provides an integrated model of patients’ expectations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
192
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 188 publications
(222 citation statements)
references
References 122 publications
6
192
0
7
Order By: Relevance
“…It is well known that many breast cancer patients feel insufficiently informed about the impact of treatment modalities on their quality of life . Moreover, accumulating evidence suggests that expectations substantially influence treatment outcome . Optimizing the management of patient expectations regarding the secondary outcomes of breast conserving therapy could thereby contribute to improved overall satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that many breast cancer patients feel insufficiently informed about the impact of treatment modalities on their quality of life . Moreover, accumulating evidence suggests that expectations substantially influence treatment outcome . Optimizing the management of patient expectations regarding the secondary outcomes of breast conserving therapy could thereby contribute to improved overall satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Second, our EXPECT intervention only focused on optimizing specific expectations such as treatment and recovery expectations and though there is a vast amount of literature on the associations between preoperative expectations and postoperative recovery, there has been no clear evidence yet which exact expectations specifically influence length of stay in CABG patients. The heterogeneity of concepts of expectations used in research is a well-known problem (56,57) which we addressed in a recent review (7). However, this is, to our knowledge, the first randomized controlled trial investigating the influence of an intervention specifically developed to optimize preoperative expectations in CABG patients and now further research is needed on precisely which expectations influence which outcomes.…”
Section: Accepted Manuscriptmentioning
confidence: 95%
“…Besides surgical procedures and medical interventions, psychological factors have a substantial predictive influence on health outcomes in heart disease (3)(4)(5). As shown in our recent reviews, expectations have been shown to be very prominent in recent research (6,7).…”
Section: Introductionmentioning
confidence: 95%
“…Trotz einer wachsenden Zahl an Studien, die die Wichtigkeit von Erwartungen im Zusammenhang mit verschiedenen medizinischen Problemen untersucht haben, ist es schwierig, die einzelnen Ergebnisse zusammenzufassen, da die Konzeptualisierung von Erwartungen und deren Erfassung sehr heterogen sind . Einen Ansatz für eine Integration bisheriger Forschungsergebnisse bietet das Integrative Erwartungsmodell von Laferton et al [2017], an dem sich dieser Artikel im Hinblick auf die Bezeichnung der Erwartungskonstrukte bereits orientiert.…”
Section: Limitationenunclassified